Psychology of the Vocal Body - Çelik, Dilara (ARTic, 2025)
It is possible to explain the psychology of the vocal body as a concept that examines the dynamic relationship between the bodily expression of the voice and mental processes. In technical terms, we can define human voice production as the timbre obtained when the air flow from the lungs vibrates the vocal cords in the larynx with high resonance. Evaluating this sound production for professional voice users is subject to many algorithms added to the existing sound production technique. Coordination of laryngeal muscles, subglottic pressure balance and resonance mechanisms, which are the basic components of vocal production, are critical for healthy voice formation. However, performance anxiety can disrupt this physiological balance, leading to fluctuations in voice quality, disruptions in breath control and increased muscle tension. In this sense, an opera singer has to manage both the aforementioned biomechanical and psychological processes during voice production. The concept of “vocal body” used in the research aims to explain not only the anatomical structures such as larynx, diaphragm and resonance cavities that contribute to voice production, but also the complex relationship of these structures with emotional, cognitive and psychological factors. On a platform where physiological and psychological processes are articulated in order to produce a quality voice suitable for intonation, it is obvious that dynamics that disrupt the body-mind integrity disrupt the quality of performance. Factors such as performance anxiety increase muscular tension, leading to laryngeal hyperfunction and ultimately to a deterioration in the timbral integrity of the voice. This proves that physiological excellence is fragile unless it is supported by psychological resilience. Only the synergy of neurobiological processes and emotional regulation can bring the vocal body to optimal performance. If we accept the concept of voice as an anatomical product of the body as well as an emotional manifestation of the mind, professional voice users must build both the product of technical production and psychological resilience through an educational philosophy that embraces this dual reality. Keywords: Vocal Body, Performance Anxiety, Body-Mind Interaction